Breastfeeding Benefits and Resources: Benefits for Babies and Mothers - Diana Hazard Taft (EDIS)
You may have heard “breast is best,” but do you know why breastmilk is the best diet for babies? Did you know that breastfeeding benefits moms, too? This publication summarizes the known benefits of breastfeeding and is written for people from all educational backgrounds.